Globalization and human rights - Brysk, Alison, 1960- (University of California Press, 2002)
In this landmark volume, Alison Brysk has assembled an impressive array of scholars to address new questions about globalization and human rights. Is globalization generating both problems and opportunities? Are new problems replacing or intensifying state repression? How effective are new forms of human rights accountability?These essays include theoretical analyses by Richard Falk, Jack Donnelly, and James Rosenau.